Wandering in darkness narrative and the problem of suffering - Stump, Eleonore, 1947- (Oxford : Clarendon, 2010)
Virtually no one would deny the extent and intensity of suffering in the world. Can one also consistently hold that there is an omniscient, omnipotent, perfectly good God? This book argues that the difficult questions raised by the problem of suffering can be considered best in the context of biblical narratives.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 9, 2010).
Keywords: Suffering -- Biblical teaching; Thomas, -- Aquinas, Saint, -- 1225?-1274.; Bible. -- Criticism, interpretation, etc